The central amygdala modulates distinctive conflict-like behaviors in a naturalistic foraging task - Kimm, Sunwhi; Kim, Jeansok J.; Choi, June-Seek (Frontiers in Behavioral Neuroscience, 2023)
Conflict situations elicit a diverse range of behaviors that extend beyond the simplistic approach or avoidance dichotomy. However, many conflict-related studies have primarily focused on approach suppression, neglecting the complexity of these behaviors. In our study, we exposed rats to a seminaturalistic foraging task, presenting them with a trade-off between a food reward and a predatory threat posed by a robotic agent. We observed that rats displayed two conflict-like behaviors (CLBs)diagonal approach and stretched posture -when facing a robotic predator guarding a food pellet. After electrolytic lesions to the central amygdala (CeA), both conflict behaviors were significantly reduced, accompanied by a decrease in avoidance behavior (hiding) and an increase in approach behavior (frequency of interactions with the robot). A significant negative correlation between avoidance and approach behaviors emerged after the CeA lesion; however, our data suggest that CLBs are not tightly coupled with either approach or avoidance behaviors, showing no significant correlation to those behaviors. Our findings indicate that the CeA plays a crucial role in modulating conflict behaviors, competing with approach suppression in risky situations.